Estudo de polimorfismos da região 3' não traduzida do gene HLA-G em pacientes portadores de hepatite B - Fontes, André Martins (2016)
The World Health Organization (WHO) estimates that about 2 billion people worldwide have had contact with the hepatitis B virus (HBV), and 240 million to become chronic carriers. Hepatitis B is a type of disease in which the pathogenetic mechanisms are not yet fully understood, and it can evolve into chronic form and promote clinical manifestations such as cirrhosis and hepatocellular carcinoma, leading to a large number of deaths annually. Considering the changes in the immune system promoted by HBV, we use a data processing through geographic information system (GIS) technology and epidemiological analysis, in the cities of the northern region of the Espírito Santo State, with the initial objective to characterize the number of individuals infected with HBV. In addition, we used this initial analysis as a basis for evaluation of gene polymorphisms that may be associated with the pathogenesis of the disease, including situated genes within the MHC as the 3 'untranslated region of the HLA-G (presence or absence of 14 pairs base, + 3001 C/T, + 3003 C/T, + 3010C/G, + 3027 A/C, + 3035 C/T, + 3142 C/G, + 3187 A/G e + 3196 C/T). A GIS and epidemiological analysis showed that São Mateus had the largest number of individuals infected with HBV, followed by the cities of Pedro Canario and Jaguaré. The population aged 20-59 years, female sex, were the most affected by the disease, where the main forms of transmission occurred through the use of injectable drugs and dental care. The main drugs used in the treatment were Tenofovir and Entecavir. Among the polymorphic sites studied in individuals of the northern state Espírito Santo and the state of Mato Grosso, only the frequency allelic +3196G [p <0.0130; (OR = 1.540; 95% CI = 1.097 to 2.162)] and frequency genotypic Del/Ins 14-bp [p <0.0194; (OR = 1.645; 95% CI = 1.101 to 2.458)] were more frequent in patients with hepatitis B compared to controls, which may be related to the encouragement of viral escape and progression of infection. Regarding the genotypes +3003C/T, +3003 TT and +3196C/C, these were more frequent in controls compared to patients and are usually associated as microRNAs target (mirRNA) being related to the degradation of mRNA, resulting in low production of soluble and membrane HLA-G isoforms. Together, considering the results found in our study, it is observed that in the north there are many patients infected with HBV, and most of the female, which may be associated with poor adherence to treatment and due to low socio-economic level, sexual transmission, and dental/medical/surgical failures by the standards of biosecurity procedures. Evaluation of genetic polymorphisms in the population suggests that they have genotypes favorable to high production of HLA-G and thus this immunoregulatory molecule could be influencing the development of the chronic form of hepatitis B and the emergence of possible complications of this disease such as liver cirrhosis and hepatocellular carcinoma.